(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
Virtual reality (VR) technology offers immersive and interactive experiences that can transform language learning, particularly in developing listening skills. This article explores the use of VR to enhance listening proficiency by creating realistic and engaging environments where learners can practice listening to authentic language inputs. It discusses theoretical foundations, benefits, practical implementation strategies, and case studies demonstrating the effectiveness of VR in improving listening comprehension and supporting language development